PENGEMBANGAN MEDIA BELAJAR BERBASIS GAME ANGRY BIRD MATEMATIKA - Dani Kusuma (Jurnal Karya Pendidikan Matematika, 2022)
This study aims to develop learning media for mathematics, especially in developing the ability of grade 1 elementary school students to perform arithmetic operations on integers using the game media Angry Bird Mathematics. The research method used in this study is the ADDIE model. The research instruments used included student observation sheets, questionnaires, and tests. The study results showed that the Angry Bird Mathematics learning media met the valid criteria as indicated by the results of expert validation, which were included in very good criteria. The practical criteria show that the Angry Bird Mathematics learning media is practically used in the learning process. Then for the indicator of the effectiveness of the learning media, it shows that the Angry Bird Mathematics learning media is effective because it can improve student learning outcomes before and after using the media.